Strategi Peningkatan Produktivitas Karyawan pada Perusahaan - Sugesti, Melisa; Gunawan, Ahmad (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2024)
This article aims to describe various strategies that companies use to increase employee productivity. This strategy refers to a careful plan to achieve a specific goal. The preparation of this strategy utilizes special methods and approaches to achieve optimal results. Employee productivity, which reflects their ability to complete tasks efficiently and effectively, is influenced by factors such as compensation, work discipline, and motivation. This research aims to analyze the impact of strategies to increase employee productivity in companies, with the aim of increasing employee efficiency at work.